PWE-031 No association between HLA-DQA1*05 and -DQB1*02 gene dosage and clinical phenotype of coeliac disease. (June 2019) - Penny, Hugo; Rees, Michael; Goodwin, John; Key, Tim; Sanders, David
Abstract : Introduction: Coeliac disease is a common gluten-sensitive enteropathy. Disease susceptibility is strongly associated with specific Human Leukocyte Antigen (HLA)-DQA1 and -DQB1 loci. Individuals with the HLA-DQA1*05:HLA-DQB1*02 heterodimer (referred to as HLA-DQ2.5) have the highest risk of developing coeliac disease, particularly if two copies of HLA-DQB1*02 are present. Understanding whether differences in the frequency of DQA1*05 and DQB1*02 accounts for differences in the clinical phenotype of coeliac disease is important for the development of personalised medicine for patients and was addressed in the following study. Methods: Demographic, clinical and laboratory data was retrospectively collected from adult patients attending the specialist coeliac disease clinic, Royal Hallamshire Hospital between 2008 to 2016 and correlated with the number of DQA1*05:DQB1*02 combinations forming the DQ2.5 heterodimer (DQ2.5 gene dose), as well as the frequency of DQB1*02. Results: Four hundred and ninety patients had biopsy-proven coeliac disease and HLA genotype information. Individuals who were positive for the DQ2.5 heterodimer were more likely to be EMA positive than those who were DQ2.5 negative (p=0.0132). There were no linear associations between the DQ2.5 gene dosage and clinical or laboratory parameters assessed. 190/490 (39%) patients carried two copies of DQB1*02, 278/490 (57%) patients had a single copy and DQB1*02 was absent in 22/490 (4%) patients. The prevalence of folate deficiency was higher and mean haemoglobin levels lower, in individuals carrying two copies of DQB1*02 than those with a single copy of DQB1*02 (p<0.001 and p=0.002, respectively), but neither were different in DQB1*02 negative individuals (p>0.05). The carriage of two copies of DQB1*02 did not correlate with any other parameters. Conclusions: The presence of DQA1*05 and DQB1*02 is well documented to correlate with risk of developing coeliac disease. Our results suggest that there is no association between homozygosity/heterozygosity for DQA1*05 and DQB1*02 and the clinical phenotype of active disease. These results provide an important insight into the interpretation of HLA-DQ data in the setting of coeliac disease.